Monitoring Urban Beach Quality on a Summer Day: Determination of the Origin of Fecal Indicator Bacteria and Antimicrobial Resistance at Prophète Beach, Marseille (France) - Toubiana, Mylène; Salles, Christian; Tournoud, Marie-George; Licznar-Fajardo, Patricia; Zorgniotti, Isabelle; Trémélo, Marie-Laure; Jumas-Bilak, Estelle; Robert, Samuel; Monfort, Patrick (Frontiers in Microbiology, 2021)
One highly attended beach of Marseille, France, was monitored hourly on a summer day of July 2018, in order to determine the possible water and sand fecal pollution in parallel with the influx of beach users from 8 am to 8 pm. Fecal indicator bacteria (FIB) were measured, together with four host-associated fecal molecular markers, chosen in order to discriminate the human, dog, horse or gull/seagull origins of the contamination. The antimicrobial resistance (AMR) of bacteria in water and sand was evaluated by quantifying i) the class 1, 2 and 3 integron integrase genes intI, and ii) blaTEM, blaCTX-M and blaSHV genes, encoding endemic beta-lactamase enzymes. The number of beach users entering and leaving per hour during the observation period was manually counted. Photographic shots of the beach and the bathing area were carried out every hour. They were used to count and distinct the number of persons in water and on the sand, using a photo-interpretation method. The number of beach users increased since early morning to peak by mid-afternoon, more than 1,800 people for such a small beach (less than 1 ha). The increase in fecal contamination in the water follows the increase in beach attendance and bathers with peaks observed from mid-afternoon. The human-specific fecal molecular marker HF183 shows that this contamination is linked to human origin. In the water, the load of Intl2 and 3 genes was lower that of Intl1 but these genes are detected only during the peak of attendance and fecal contamination. The dynamics of genes encoding B-lactamases involved in B-lactams resistance were particularly linked to the attendance and to human fecal contamination. Fecal indicator bacteria, integron integrase genes intI and genes encoding B-lactamases were present in the sand. This study shows that bathers and beach users could be high contributors to the contamination of sea water and beach sand by bacteria of fecal origin but also by bacteria carrying integron-integrase genes and beta lactamase encoding genes. The situations of high influx of users on the beaches should also be taken into account to reduce contamination and manage sanitary risks.